Carbon Emissions Disclosure, Environmental Management System, and Environmental Performance: Evidence from the Plantation Industries in Indonesia - Pikar Setiawan; Sri Iswati (Indonesian Journal of Sustainability Accounting and Management, 2019)
This study aims to examine the relationships between the environmental management system, environmental performance, and carbon emissions disclosure in Indonesia, a country with rich natural resources. The study focuses on the plantation industries so as to better capture the disclosure behavior of companies directly engaged in natural resources. They were all registered on the Indonesian Stock Exchange (IDX) from 2013 to 2017. The testing of the hypotheses uses multiple linear regressions. Test-F shows a model that is stable and significant. The research results show two variables that have been proven to be insignificant with regard to carbon emissions, namely the environmental management system and leverage. Research further proves that ISO 14001 and leverage did not affect the commitment to express carbon emissions. Environmental performance and age firms in this research have affected positive and significant impacts on disclosure of carbon emissions in the plantation industries. This demonstrates that companies that receive the PROPER Awards from the Ministry of Environment and Forestry are those with good environmental performance in accordance with government regulations to reduce greenhouse gas emissions.